2008
DOI: 10.1158/1535-7163.mct-08-0514
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatocellular carcinoma in mice with PE38KDEL type I mutant-loaded poly(lactic-co-glycolic acid) nanoparticles conjugated with humanized SM5-1 F(ab′) fragments

Abstract: We reported previously the development of SMFv-PE38K-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…These results firmly demonstrated that anti-EGFR Fab' conjugation could specifically enhance the binding affinity of TLPD-FCC in breast cancer cells of high or moderate EGFR expression, but not in cells with low EGFR expression. These results were consistent with our previous results about the in vitro targeting efficiency of targeted nanoparticles in hepatocellular carcinoma cell lines with different tumor specific antigen expression [24].…”
Section: Transfection Efficiency Of Tlpd-fccsupporting
confidence: 93%
“…These results firmly demonstrated that anti-EGFR Fab' conjugation could specifically enhance the binding affinity of TLPD-FCC in breast cancer cells of high or moderate EGFR expression, but not in cells with low EGFR expression. These results were consistent with our previous results about the in vitro targeting efficiency of targeted nanoparticles in hepatocellular carcinoma cell lines with different tumor specific antigen expression [24].…”
Section: Transfection Efficiency Of Tlpd-fccsupporting
confidence: 93%
“…Proliferation of SK-BR3 and MCF-7 cells was measured by Cell Titer 96 nonradioactive cell proliferation assay kit according to the manufacturer's protocols (Promega, Madison, WI) as described before [22]. Briefly, the cells were seeded into 96-well plates (3 Â 10 4 cells per well) and incubated overnight.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…Gao et al also developed PE38KDEL type I mutant-loaded PLGA NPs conjugated with SM5-1 mAb F(ab'). 147 The results showed that the NPs were specifically internalized into Ch-hep-3 cells with high efficiency and exhibited potent cytotoxicity of hepatoma cells.…”
mentioning
confidence: 95%